Economic dynamics versus institutions in the research approach to evolutionary economics - Grodzicki, Maciej (Journal of Public Governance, 2014)
The purpose of the article is to demonstrate how contemporary evolutionary economics tries to incorporate the institutional aspect into its research on economic change. The author presents an overview of the major positions found in this school of economic thought in order to, first, describe this rapidly developing and still little known in Poland approach to economic analysis, and, second, reflect on the usefulness of selected attempts to include the institutional aspect to the research programme. The evolutionary economics approach sheds light on the problems and phenomena overlooked by mainstream economics, especially by focusing on the dynamic nature of capitalism. In the presented model of the relationship between microeconomic activities and aggregated macroeconomic results, institutions are a necessary complement. In many ways, they affect the activities of economic actors and determine the functioning of mechanisms of aggregation of economic performance, but they are also themselves subject to evolutionary change.